Mechanisms of Antibiotic Tolerance in Mycobacterium avium Complex: Lessons From Related Mycobacteria - Parker, Harley; Lorenc, Rachel; Ruelas Castillo, Jennie; Karakousis, Petros C. (Frontiers in Microbiology, 2020)
Mycobacterium avium complex (MAC) species are the most commonly isolated nontuberculous mycobacteria to cause pulmonary infections worldwide. The lengthy and complicated therapy required to cure lung disease due to MAC is at least in part due to the phenomenon of antibiotic tolerance. In this review, we will define antibiotic tolerance and contrast it with persistence and antibiotic resistance. We will discuss physiologically relevant stress conditions that induce altered metabolism and antibiotic tolerance in mycobacteria. Next, we will review general molecular mechanisms underlying bacterial antibiotic tolerance, particularly those described for MAC and related mycobacteria, including M. tuberculosis, with a focus on genes containing significant sequence homology in MAC. An improved understanding of antibiotic tolerance mechanisms can lay the foundation for novel approaches to target antibiotic-tolerant mycobacteria, with the ultimate goal of simplifying and shortening MAC treatment.